Experimental investigations of the effect of the mode-hopping on the noise properties of InGaAsP Fabry-Perot multiple-quantum-well laser diodes. - Palenskis, V.
Detail studies of the optical and electrical low-frequency noise spectra and their correlation factor of graded-index separate-confinement-heterostructure, multiple-quantum-well (MQW) strained-layer Fabry-Perot (FP) InGaAsP/InP laser diodes have been carried out. It is shown that at defined DC currents and temperatures the intensive Lorentzian-type optical and electrical noise peaks (mode-hopping effect) of the FP lasers may be caused by different effects, since the correlation factor between the noises may be positive, negative, or close to zero, i.e., the diode terminal voltage (or resistance) and light output power can fluctuate in phase, in opposite phases or independently. It is determined that the shift of noise peak due to variation of temperature has an activated character. The activation energy is equal to nearly half the bandgap energy of the barrier layer or region, adjacent to the active region of the laser. It was also shown that coating the FP laser diode mirrors by a thin dielectric layer causes a substantial suppression of the mode-hopping effects, with only a small change of the light output power: i.e., the noise peaks are strongly related to the charge carrier and photon confinement in the active region and neighboring to the active regions.
Keywords: GRINSCH MQW structures; InGaAsP Fabry-Perot laser diodes; InGaAsP-InP.; InGaAsP/InP laser diodes; Lorentzian-type electrical noise peaks; Lorentzian-type optical noise peaks; Activation energy; Charge carrier confinement; Correlation factor; Diode terminal voltage; Electrical LF noise spectra; Graded-index separate confinement heterostructure; Laser diode mirrors; Laser facet coating; Light output power; Mode-hopping effect; Multiple quantum well LDs; Noise properties; Optical noise spectra; Photon confinement; Semiconductor lasers; Thin dielectric layer